TINDAK TUTUR ILOKUSI PADA NOVEL ZAINY BARAKAT KARYA GAMAL AL GHITANI (KAJIAN PRAGMATIK) - Fitriya, Nofita Indah; Rahmawati, Nailur; Arifin, Akbar Syamsul (Universitas Negeri Semarang, 2021)
The objectives of this research are; (1) Identifying the form of illocutionary speech acts found in Gamal Al Ghitani's Zainy Barakat novel; (2) Determine the pragmatic function of illocutionary speech acts contained in the novel Zainy Barakat by Jamal Al Ghitani.This research is a qualitative research, the research design is in the form of a literature study (study research), the data collection technique is a note-taking technique, the research instrument uses data cards and data recapitulation sheets, while the data analysis method uses the extralingual equivalent method. In this study research, 155 speech acts were found which were divided into 5 forms of illocutionary speech acts and 4 speech act functions. Based on the analysis of the utterances, it can be detailed as follows; 43 forms of assertive illocutionary speech, 61 forms of directive illocutionary speech, 11 forms of speech illocutionary commissive, 38 forms of expressive illocutionary speech, and 2 forms of declarative illocutionary speech. Of the five forms of illocutionary speech, directive speech is the most common, and the form of declarative speech is the least used. Pragmatic functions are classified into four kinds of functions, namely competitive, conventional, collaborative and conflictual. In the novel Zayni Barakat found four kinds of functions which are detailed as follows: 58 competitive functions, 28 conventional functions, 47 ​​collaborative functions and 22 conflictive functions. From these data, the most pragmatic function found is the competitive function, and the least is the conflictive function.